2018
DOI: 10.1371/journal.pone.0203631
|View full text |Cite
|
Sign up to set email alerts
|

Development of a novel S. Typhi and Paratyphi A outer membrane vesicles based bivalent vaccine against enteric fever

Abstract: Salmonella Typhi and Salmonella Paratyphi A are the leading causative agents of enteric fever which cause morbidity and mortality worldwide. Currently, there is no combination vaccine which could protect infection from both the strains. In this paper, we are focusing on the development of a novel bivalent typhoidal Outer Membrane Vesicles (OMVs) based immunogen against enteric fever. We have isolated Salmonella Typhi and Paratyphi A OMVs and also characterized OMVs associated antigens. Then we immunized adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 74 publications
2
10
0
2
Order By: Relevance
“…OMV immunization ultimately leads to a reduction in bacterial colonization in immunized animals but not in nonimmunized animals. The serum bactericidal assay results showed that our immunized animal sera killed H. pylori in the presence of complement compared to the nonimmunized animal sera (31,64,65).…”
Section: Clinical Detection Of H Pylori Infection Generally Involves ...mentioning
confidence: 89%
“…OMV immunization ultimately leads to a reduction in bacterial colonization in immunized animals but not in nonimmunized animals. The serum bactericidal assay results showed that our immunized animal sera killed H. pylori in the presence of complement compared to the nonimmunized animal sera (31,64,65).…”
Section: Clinical Detection Of H Pylori Infection Generally Involves ...mentioning
confidence: 89%
“…The OMVs have received increasing attention as a vaccine delivery platform in recent years. Howlader et al (2018) developed an oral bivalent typhoid vaccine by mixing the OMVs from S. Typhi and S. Paratyphi A in a 1:1 formulation. Oral immunization of BALB/c mice with the bivalent OMVs at a 2-week interval elicited strong responses of mucosal immunity, humoral immunity and cell-mediated immunity.…”
Section: An Oral Bivalent Vaccine Candidate Based On Outer Membrane V...mentioning
confidence: 99%
“…Oral immunization of BALB/c mice with the bivalent OMVs at a 2-week interval elicited strong responses of mucosal immunity, humoral immunity and cell-mediated immunity. The vaccination protected the immunized mice from the lethal challenges of S. Typhi as well as S. Paratyphi A (Howlader et al, 2018).…”
Section: An Oral Bivalent Vaccine Candidate Based On Outer Membrane V...mentioning
confidence: 99%
“…Formulations of Neisseria meningitidis OMVs (VA-MENGOC-BC, MenBvac, MeNZB and Bexero) have been successfully used to vaccinate both adults and children and to control outbreaks of meningococcal B infection in several countries [100,101]. OMVs from other Gram-negative pathogens are also promising vaccine candidates, including those from Salmonella [102], Shigella flexneri [103] and V. cholerae [104]. However, their potential for unintended toxicity due to associated toxins is a safety concern and limits their widespread use, although chemical detoxification can overcome this, but at the loss of immunogenicity and adjuvanticity [105].…”
Section: Improving Mucosal Vaccinesmentioning
confidence: 99%